The Relationship between Characteristics of Chronic Obstructive PulmoNary Disease Patients and Spirometry Results (FEV1) in the Treatment Room of Waled Regional Hospital, September 2023-September 2024 - Nadiyah Athirasaffa; Dwi Rosa Eka Agustina; Rian Damayanti (International Journal of Health and Pharmaceutical (IJHP), 2026)
Chronic Obstructive Pulmonary Disease (COPD) is the fourth leading cause of global mortality with a high prevalence in Indonesia (3.7%), dominated by demographic factors such as advanced age and occupational exposure in rural areas such as Cirebon Regency, however, analytical studies of the relationship between patient characteristics and lung function (FEV1) are still minimal. This study aims to analyze the description and relationship of age, gender, and occupational history of COPD patients with FEV1 spirometry results. Using a cross-sectional analytical observational design on medical record data of 131 adult patients (>26 years) at Waled Regional Hospital from September 2023–September 2024 via total sampling, bivariate analysis was performed using Spearman Rank and Chi-Square tests (SPSS 26, α=0.05). The results showed that the majority of patients were elderly (>65 years, 45.04%), male (67.94%), construction workers (31.30%), and very severe (<30% FEV1, 62.60%); There was a weak positive significant association between age (p=0.040; r=0.180) and gender (p=0.045; r=0.176), but no significant association was found for occupation (p=0.450). The study concluded that demographic factors influence COPD progression, recommending routine risk-based spirometry screening to optimize prognosis in primary care settings